MULTIKULTURAL MENURUT HUKUM ISLAM DAN APLIKASINYA DALAM PENDIDIKAN - Yuldafriyenti; Lizi Virma Surianti; Elpita Sari; Rusydi; Karim, Shofwan; Wahyuni, Sri; Yunaldi, Wendra (Institut Agama Islam Hamzanwadi NW Lombok Timur, 2025)
Abstract. In Indonesia, we cannot escape from multiculturalism. The philosophy of multiculturalism encourages people to respect and interact with each other regardless of their status or origin. Multiculturalism is viewed by Islamic law as a natural and divine desire that must be upheld. Islamic values ​​such as justice, brotherhood, and tolerance offer a standard basis for resolving differences peacefully. Qualitative is the method used and the technique of collecting library study data. It is done by looking at reading sources that have the same research topic. The data taken is through books, scientific journals and other digital sources. Multiculturalism is a useful tactic in education to create a generation that is accepting, tolerant, and aware of religious values. Islamic law states that the purpose of multicultural education is to instill the values ​​of justice, equality, and tolerance. Islamic-based multiculturalism can build a learning environment that supports communication and collaboration between cultures while preserving Islamic principles. Therefore, multicultural education in accordance with Islamic law can be a way to create a just, civilized, and peaceful society despite differences. Keywords: Multicultural, Multicultural Education, Multicultural Education Of Islamic Law